Thermofluidic chip containing virtual thermal wells - Andrew J. Ferguson; Matthew J. Hayes; Blair C. Kirkpatrick; Yen-chun Lin; Vijay Narayan; Albert Prak; Albert Prak (Engineering Biology, 2019)
The authors describe a thermofluidic chip on which microscale islands of controlled temperature are formed within an open fluidic environment. The chip forms part of the authors’ technology for thermally controlled DNA synthesis, whereby the site-specific temperature control enables site-specific addressability of chemical reactions, for example, related to the phosphoramidite cycle. Here, the authors discuss the principle of the chip, supporting the thermal well concept by means of simulations as well as by showing a prototype thermal array device.